β-cyclodextrin chitosan-based hydrogels with tunable pH-responsive properties for controlled release of acyclovir: design, characterization, safety, and pharmacokinetic evaluation - Nadia Shamshad Malik; Mahmood Ahmad; Mohammed S. Alqahtani; Arshad Mahmood; Kashif Barkat; Muhammad Tariq Khan; Ume Ruqia Tulain; Ayesha Rashid (Taylor & Francis Group, 2021)
In this work, series of pH-responsive hydrogels (FMA1-FMA9) were synthesized, characterized, and evaluated as potential carrier for oral delivery of an antiviral drug, acyclovir (ACV). Different proportions of β-cyclodextrin (β-CD), chitosan (CS), methacrylic acid (MAA) and N' N'-methylenebis-acrylamide (MBA) were used to fabricate hydrogels via free radical polymerization technique. Fourier transform infrared spectroscopy confirmed fabrication of new polymeric network, with successful incorporation of ACV. Scanning electron microscopy (SEM) indicated presence of slightly porous structure. Thermal analysis indicated enhanced thermal stability of polymeric network. Swelling studies were carried out at 37 °C in simulated gastric and intestinal fluids. The drug release data was found best fit to zero-order kinetics. The preliminary investigation of developed hydrogels showed a pH-dependent swelling behavior and drug release pattern. Acute oral toxicity study indicated no significant changes in behavioral, clinical, or histopathological parameters of Wistar rats. Pharmacokinetic study indicated that developed hydrogels caused a significant increase in oral bioavailability of ACV in rabbit plasma as compared to oral suspension when both were administered at a single oral dose of 20 mg kg−1 bodyweight. Hence, developed hydrogel formulation could be used as potential candidate for controlled drug delivery of an antiviral drug acyclovir.